Insurgency in Southern Thailand: what does ISIL's black flag of Pattani portend? - Rajakumar, Vikram (2016)
Recent online activity by Southern Thai radicals highlight the emergence of a new ISIL-inspired threat. While promoting autonomy for the Muslim majority provinces online radicalisation has the potential to become a precursor for real world violence.